Assessing the Viability of Crowd Logistics for Last-mile Delivery: Case Studies in Malaysia Logistics Industry - Nor Rokiah Hanum, Md Haron; Lee, Khai Loon; Nawanir, Gusman (Universiti Teknologi MARA Cawangan Terengganu, 2023)
This study focuses on crowd logistics challenges in Malaysian crowd logistics companies. To the author's best knowledge, there is limited empirical qualitative research on crowd logistics, especially in the Malaysian logistics sector. This research aims to identify and examine the challenges that hinder the success of crowd logistics and how crowd logistics can shape the future of the logistics industry. A semi-structured interview with six industry experts, including logistics service providers and platform operators, were selected in this study to gain insights into their experiences and perspectives on crowd logistics. Additionally, a data analysis process is presented. The findings of this study suggested three main themes and six sub-themes, including operation management, resource management, and technology and communication management as the main themes. The sub-themes include delivery operation, service offered, rider issues, demand issues, delivery platform, and technology implementation issues. This study provides implications in two-fold. First, for the theoretical implication, it provides empirical case studies and highlights critical challenges faced by crowd logistics companies in Malaysia. Secondly, for practical implications, it offers valuable insights for logistics companies, especially those engaged in crowd logistics, to understand the challenges customers and service providers face. However, this research is limited in its generalizability and triangulation studies which calls for further investigation.